Union Density, Coverage and Recognition: A Previous Study Analysis - Muzdalifah Jangli; Fazli Abd Hamid (2018)
The literature review shows the various studies made by Industrial Relations scholars on the movement of trade unions worldwide. The trade union’s movement definitely shapes the industrial relations system. This is because trade union is one of the factors that have the goal of preserving and protecting the welfare and importance of the workers’ rights. This research uses the secondary analysis method that emphasizes on the three elements that considered vital in determining the strength of trade union, namely unity density, union coverage and union recognition. The objective of this article is to identify the key element between the three elements of union strength that are often applied based on previous studies. This article finds that each of these three elements is classified separately, whereas the summary of these three need to be made as studies on the strength of trade unions can be explored more clearly by using the factors of union density, coverage and union recognition. Secondly, the latest research especially that emphasizes on the union’s coverage is still limited. A study that emphasizes on the coverage of the union should be emphasized as it depicts the solidarity of current trade unions.